The Feasibility Analysis of the Smoke Fish Business in Bone Village Kulisusu District Buton Utara Regency - Pusran Pusran; R. Marsuki Iswandi; Fahria Nadiryati Sadimantara (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2023)
This research was motivated by the production, income, and feasibility of the smoked fish business in Bone Village, Kalisusu District, North Buton Regency. The objectives of this research are: (1). Analyzing the amount of smoked fish business production in Bone Village, Kulisusu District, North Buton Regency. (2) Analyze the smoked fish business income in Bone Village, Kulisusu District, North Buton Regency. (3). Analyzing the feasibility of the smoked fish business in Bone Village, Kulisus District, North Buton Regency. The sampling technique in this study was determined by the saturated sampling technique in which all 15 business actors were sampled. Data analysis in this study uses the formula for revenue, income, and total production costs, while business feasibility analysis uses BEP, ROI, and R/C Ratio analysis. The results of this study are: (1) The amount of production of smoked fish business is 5129 kg for a year (2) The average amount of income/year is Rp. 88,945 (3) Smoked fish business in Bone Village can be said to be profitable, based on the calculation of feasibility analysis. The production BEP value is 2,588kg, and the BEP price is Rp. 35,000, the ROI calculation value is 98%, and the R/C ratio is 1.98.